Optimizing public interests through competitive tendering : concept, context and challenges / edited by Chris Jansen [and three others]. - Jansen, Chris (Cambridge University Press, 2025)
Governments are increasingly trying to achieve a variety of public interests through competitive tendering of public contracts, authorisations, subsidies as well as public assets. Over the past decades, domestic and EU law has developed for these 'limited rights' at different speed and is extremely fragmented: there is no coherent legal framework. This book provides information on the legal aspects of competitive allocation of all types of limited rights on the basis of an overarching perspective. It explains the impact of the legal framework on the ability of governments to achieve the public interests they pursue through competitive tendering. The book is relevant for domestic and EU public authorities, legislators, courts of law, as well as academics. It discusses and connects in a consistent manner, legal questions arising in the framework of competitive allocation of public contracts, authorisations, subsidies and public assets.